1998
DOI: 10.1093/hmg/7.13.2095
|View full text |Cite
|
Sign up to set email alerts
|

NF2 gene in neurofibromatosis type 2 patients

Abstract: Neurofibromatosis type 2 (NF2) is an autosomal dominant disorder that predisposes to nervous system tumors. The schwannomin (also termed merlin) protein encoded by the NF2 gene shows a close relationship to the family of cytoskeleton-to-membrane proteins linkers ERM (ezrin-radixin-moesin proteins). Even though penetrance of the disease is >95% and no genetic heterogeneity has been described, point mutations in the NF2 gene have been observed in only 34-66% of the screened NF2 patients, depending on the series.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 30 publications
4
49
0
Order By: Relevance
“…Of the 16 intragenic alterations not removing either the initiator codon or native stop, 12 would be predicted to produce in-frame deletions and four out-of-frame deletions. A total of 29 constitutional gene-or chromosome-level gross rearrangements have been reported in NF2 patients, including four ring chromosome 22 cases [Kehrer-Sawatzki et al, 1997;Tsilchorozidou et al, 2004]; two translocations [Tsilchorozidou et al, 2004], and 23 complete gene deletions Trofatter et al, 1993;Watson et al, 1993;Evans et al, 1998;Zucman-Rossi et al, 1998;Bruder et al, 2001;Wallace et al, 2004;Diaz de Stahl et al, 2005;Kluwe et al, 2005;Sestini et al, 2005]. Because a much smaller number of samples have been studied with these techniques than with those used to determine small intragenic changes, further work is needed to understand the full spectrum of rearrangements involving the NF2 locus.…”
Section: Mutations and Polymorphisms Nf2 Constitutional Alterationsmentioning
confidence: 99%
“…Of the 16 intragenic alterations not removing either the initiator codon or native stop, 12 would be predicted to produce in-frame deletions and four out-of-frame deletions. A total of 29 constitutional gene-or chromosome-level gross rearrangements have been reported in NF2 patients, including four ring chromosome 22 cases [Kehrer-Sawatzki et al, 1997;Tsilchorozidou et al, 2004]; two translocations [Tsilchorozidou et al, 2004], and 23 complete gene deletions Trofatter et al, 1993;Watson et al, 1993;Evans et al, 1998;Zucman-Rossi et al, 1998;Bruder et al, 2001;Wallace et al, 2004;Diaz de Stahl et al, 2005;Kluwe et al, 2005;Sestini et al, 2005]. Because a much smaller number of samples have been studied with these techniques than with those used to determine small intragenic changes, further work is needed to understand the full spectrum of rearrangements involving the NF2 locus.…”
Section: Mutations and Polymorphisms Nf2 Constitutional Alterationsmentioning
confidence: 99%
“…8,9,21,22,33,36,43,50,58,61,62,70,71,77 Abnormalities of the NF2 gene are also found in malignant mesothelioma, tumors that are not typically associated with neurofibromatosis. 26, 67 The presence of multiple meningiomas/schwannomas in an individual usually implies that there is a germ line mutation (with every cell in the body containing that mutation) or that the patient is a mosaic for a particular mutation (a proportion of cells within the individual's tissues harbor a mutation as a result of a postzygotic event).…”
Section: Overviewmentioning
confidence: 99%
“…A majority of the mutations are nonsense, frameshift, or spliced donor site mutations, all of which result in a nonfunctional, trun- cated protein. More recently, it was found that large deletions in the NF2 may be present in NF2 patients, raising the frequency of detectable NF2 alterations in this population to 84% (Zucman-Rossi et al, 1998). Development of bilateral vestibular schwannomas is a typical feature of NF2.…”
Section: Nf2 and Nf1 Status In Conventional Schwannomasmentioning
confidence: 99%